Pengaruh penyuluhan kesehatan terhadap personal hygiene pada siswa SD Katolik 15 St. Laurentius Kota Manado - Sutjiato, Margareth; Mongi, Thirsa (UNIVERSITAS SAM RATULANGI, 2024)
Background: Personal hygiene is self-care that is done to maintain health, both physically and psychologically. Personal hygiene is a basic human need that must always be fulfilled. Personal hygiene is included in specific primary prevention measures. Personal hygiene is very important because good personal hygiene will minimize the entrance (port de entry) of microorganisms that are everywhere and ultimately prevent a person from getting sick. Aim: To determine the effect of health counseling on personal hygiene in students of Catholic Elementary School 15 St. Laurentius, Manado City. Methods: This research is a pre-experiment study and uses a one group pre-test post-test design in August 2024 and the research site at SD Katolik 15 St. Laurentius Kota Manado. The sampling technique used a total population of 16 The statistical test used was the statistical test “t-test” with a 95% confidence degree. Results: The results of the study obtained Personal Hygiene Research on Students at Catholic Elementary School 15 ST. Laurentius Manado City before giving health counseling. More are less than good. The results of Personal Hygiene research on students at Catholic Elementary School 15 ST. Laurentius City Manado after Giving Health Counseling more are good than less. there is an effect of health counseling on personal hygiene in students of Catholic Elementary School 15 St. Laurentius City Manado. Conclusion: There is an effect of health counseling on personal hygiene in students of Catholic Elementary School 15 St. Laurentius City Manado Suggestions in this study are This research is expected to help students understand the importance of personl hygiene in preventing disease. Keywords: health counseling, personal hygiene for students